LEGAL AND PRACTICAL ISSUES IN THE MANAGEMENT OF WAQF PROPERTIES IN SRI LANKA - Saujan, Iqbal; Mazahir, Seyed Mohamed Mohamed (International Journal of Sukuk and Waqf Research, 2021)
Waqf (Endowment) is the permanent dedication extended by a Muslim to any movable or immovable property for a purpose recognized by the Shari’ah as pious, religious, or charitable. This is one of the Islamic institutions that have existed since the time of the Prophet (PBUH). The Sri Lankan management operations of Waqf were exercised institutionally as early as 1956. Due to the improper management of waqf assets, society has faced several problems such as poverty, unemployment, recession in education. Therefore, this study aims to identify the legal and practical challenges faced by Waqf institutions in terms of proper implementation of the Muslim Mosques and Charitable Act- 1956 (Wakfs Act of Sri Lanka). The method of the qualitative study was used. The findings demonstrate that there is no authority to the waqf Tribunal to amend a verdict, the Waqf Tribunal depends on the District Courts in implementing the judgments and there are deficiencies in the selection of trustees or mutawallis. This study concludes with the argument that the institutional process of the Sri Lankan Waqf act has legal and practical shortcomings. If these shortcomings are minimized there is no doubt that this Islamic waqf system will help to develop Sri Lanka economically.